RELIGIOSITY AND ETHICAL BEHAVIOR AS DETERMINANTS OF WHISTLEBLOWING INTENTION AND PERFORMANCE IN THE IMPLEMENTATION OF CLEAN AND SERVING BUREAUCRATIC AREA - Mahesa, Gigih Jati; Ratnaningsih, Stephana Dyah Ayu (Jurnal Akuntansi Bisnis, 2025)
Background: In an increasingly dynamic business world, integrity and ethics are important pillars for the continuity and reputation of the company. Optimal employee performance is influenced by the application of ethics and integrity, which can also reduce the risk of fraud. To deal with potential fraud, some institutions have implemented a whistleblowing system, which allows employees to report unethical or illegal actions.Objective: This study aims to examine the effect of religiosity and ethical behavior on employee performance and intention to whistleblowing.Research Methods: This study examined employees at a government agency in Semarang, Central Java, with a population of 650 employees. Based on recommendations from previous research, the sample was drawn using the Proportionate Stratified Random Sampling method due to the heterogeneous and stratified population. From this population, 86 samples were calculated using the Slovin formula with a tolerance of 0.1, but increased to 121 to avoid questionnaire completion errors. Data collection was conducted through an online questionnaire with Google Form to 105 respondents, aiming for time and cost efficiency.Research Results: Religiosity and ethical behavior have a positive influence on employee performance and whistleblowing intentions. A higher understanding of religiosity encourages a greater sense of responsibility, thus improving performance. Ethical behavior also contributes positively to performance because good ethics help achieve company goals. In addition, religiosity and ethical behavior significantly influence whistleblowing intentions, where faithful and ethical individuals are more likely to report fraud in the company, especially in an environment that supports corruption-free rules and whistleblowing systems.Authenticity/Novelty of Research: his study examines how the rules and criteria of WBBM strengthen ethical behavior and whistleblowing intention. It also highlights the role of WBBM in promoting transparency and accountability as part of bureaucratic reform and fraud prevention.